The Role of Motor Competences in Predicting Working Memory Maintenance and Preparatory Processing. Issue 3 (21st February 2019) - Ludyga, Sebastian; Mücke, Manuel; Kamijo, Keita; Andrä, Christian; Pühse, Uwe; Gerber, Markus; Herrmann, Christian
Abstract : The purpose of the study was the examination of the longitudinal association between motor competences and changes in preparatory processing during a task requiring working memory maintenance. At baseline, 52 Caucasian children aged 10–12 years completed the MOBAK‐5 test battery and a Sternberg task, whereas the cue‐P300 and the initial contingent negative variation (iCNV) were recorded via electroencephalography. After 9 months, the Sternberg task was administered again to assess changes in these neurophysiological indices and behavioral performance. Path analyses revealed that motor competences predicted the change in cue‐P300 and iCNV from baseline to follow‐up. The present findings indicate that the cognitive control strategy during a task demanding working memory maintenance changes as a function of children's baseline motor competences.